RESEARCH ON TORSIONAL STIFFNESS MATCHING AND VISUALIZATION METHOD OF VEHICLE BODY - HUANG Bin; HU ZhaoHui; LUO DeYang (Jixie qiangdu)
The present torsional stiffness calculation and evaluation method only reflect the body stiffness and the torsion curves of the cross beam or threshold,it can hardly be used to evaluate the stiffness matching characteristics and the contribution of local region in body comprehensively. Aiming at this problem,a stiffness evaluation method based on regional contribution was proposed,with the strain energy and strain energy density as analyzed object. Meanwhile,a visualization method was proposed to visualize the regional contribution values. The methods above were applied to a domestic commercial vehicle. The contribution visualization model of body framework was established and the body stiffness matching characteristics were analyzed. The torsional stiffness matching was more reasonable after structure optimization. It indicates that the contribution visualization model can be used to evaluate stiffness matching characteristics of body and the contribution of each region intuitively,which gives guidance to structure stiffness matching design.